Belonging through a psychoanalytic lens - Coleman Curtis, Rebecca (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Watching people protest, one hypothesis is that underlying these actions for specific justifiable causes, is a sense of wishing to belong, of wishing not to be alone. Recent knowledge from patients and empirical research shows the importance of belonging to groups both to psychological and physical well-being. The problems of many students, minority group members, immigrants, terrorists, and many lonely people are linked to an insufficient sense of belonging. Whereas psychoanalytic theory has focused on the need for a secure attachment to a primary caretaker, it has failed to note the importance of a sense of belonging to the family group, a friendship group, a community, a religious group, a nation-state, etc. This book demonstrates the difficulties faced by those who immigrate, those who never feel a sense of their true selves as belonging in a family, a cohesive professional group, and the difficulties of psychoanalysts themselves in knowing where they belong in patients' lives. The problems of breaking up marital and professional relationships as well as our relationship with the earth are also discussed. Freudian theory rejected the idea of a sense of "oneness" with humanity as being infantile. Recent developments regarding the similarities between meditational practices and psychoanalysis have questioned Freud's idea. This book shows the importance of an interpersonal/relational psychoanalysis focusing on real relationships and not simply one that examines inner conflicts. It will be useful to psychologists,"--
OCLC-licensed vendor bibliographic record.
Keywords: Belonging (Social psychology); Social isolation; PSYCHOLOGY / Movements / Psychoanalysis; PSYCHOLOGY / Mental Health